(untitled) (International Journal of Engineering and Computer Science, 2017)
Objects of everyday life will be equipped with microcontroller, microprocessor, embedded system and transceivers for digital communication with one another and with the users, becoming an integral part of internet. In this paper, we focus specifically to an urban internet for atmospheric parameter system. Through the mechanism of internet, we make a modem specially focused on atmospheric parameter which consists of three sensors for air, noise pollution and temperature measurement and the controlling of street light thus connected to the embedded system. This transmitted the data to the server and received by the pc or GUI modem. For this, modem is designed to support SMART CITY vision, which aims at exploiting the most advanced communication technologies to support added-value services for the administration of the city and for the citizens